Knowledge, Attitude and Practice Towards Droplet and Airborne Isolation Precautions Among Dental Health Care Professionals in Shiraz, Iran - Mehrdad Askarian, MD, MPH; Kamran Mirraei, MD, MPH; Behnam Honarvar MD, MPH; Mahyar Etminan, PharmD (Blackwell Synergy, 2005)
To determine the level of knowledge, attitude and practice among Iranian dental health care professionals towards droplet and airborne isolation precautions, in Shiraz, Iran.